How does work engagement mediate the association between human resources management and organizational performance? - Pombo, Gonçalo (2022)
The aim of this paper is to understand how workers’ perceptions and behaviors contribute to understanding the association between human resources management (HRM) and organizational performance (OP). Over the past few decades, theory construction has lagged the intermediate linkages between HRM and OP, and, therefore, there are still many unanswered questions with regards to such an association. To sustain the HRM-OP link, the authors highlight the potential influence of employees’ work engagement (WE), with the aim of exploring some of the intermediating variables, focusing on the perceptions of employees’ attitudes and behaviors. This research emphasizes that line managers have a crucial role to play in stimulating employees’ efforts and in shaping HR-related outcomes. Line managers act as crucial intermediaries in determining how HR policies that lead to OP can be designed and administered. Nevertheless, line managers have the capability to disrupt or stimulate the system, which has a significant impact on employees’ engagement with the organization. The empirical research is based on a sample of 1,609 employees and 40 organizations and was carried out in two settings. Results suggest that line managers and employees’ perceptions of HR policies were positively related to line managers’ perceptions of OP. The results also support a path model, whereby WE strengthens HR systems’ association with enhanced levels of OP. The discussion reviews the implications of these results and suggests future directions for research.